Anti-aging bronze powder pigment as well as preparation method and application thereof

By constructing a multi-layer composite system, copper-gold powder pigments achieve ultimate weather resistance and super strong interlayer bonding under the premise of environmental protection, solving the problem of insufficient aging resistance of traditional copper-gold powder pigments and meeting the requirements of the automotive manufacturing industry for durability and metallic shimmer effect.

CN121136482AActive Publication Date: 2025-12-16INNER MONGOLIA XUYANG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202511682159.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2025-12-16
Estimated Expiration
2045-11-17

AI Technical Summary

Technical Problem

Traditional copper-gold powder pigments have poor resistance to environmental aging, especially insufficient resistance to ultraviolet aging, which cannot meet the requirements of the automotive manufacturing industry for long-term durability and metallic luster. Existing surface treatment methods have problems such as insufficient protective efficacy, weak interfacial bonding, difficulty in balancing long-term UV resistance and physical barrier performance, and difficulty in unifying environmental protection and high performance.

Method used

The design employs a multi-layer composite system, including a composite chemical passivation layer, a functionalized organic-inorganic hybrid dense barrier layer, and a superhydrophobic surface layer. These layers are connected by chemical bonds and covalent bonds to form a four-layer structure: "sheet-like copper-zinc alloy substrate - composite chemical passivation layer - functionalized organic-inorganic hybrid dense barrier layer - superhydrophobic surface modification layer". This achieves extreme weather resistance, strong interlayer bonding, and long-lasting UV protection.

Benefits of technology

It achieves long-term durability and metallic decorative texture of copper-gold pigments under extreme conditions, meeting the stringent requirements of automotive coatings for both durability and visual texture, and solving the problems of easy oxidation of traditional copper-gold pigments under ultraviolet light and the inability to achieve both optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121136482A_ABST
    Figure CN121136482A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-aging bronze powder pigment and a preparation method and application thereof in the technical field of bronze powder pigments, and the anti-aging bronze powder pigment takes copper-zinc alloy as a base material, and is sequentially connected with a composite chemical passivation layer, a functionalized organic-inorganic hybrid compact barrier layer and a surface super-hydrophobic layer through chemical bonding from inside to outside; wherein the composite chemical passivation layer is formed by treating a passivation solution containing phytic acid, ammonium metavanadate and sodium tungstate; the functionalized organic-inorganic hybrid compact barrier layer is constructed by a silane mixed solution containing 3-mercaptopropyltriethoxysilane, a reaction type ultraviolet light absorber Si-BP, a reaction type hindered amine light stabilizer Si-HALS and tetraethyl orthosilicate through a sol-gel process. Through the design of a multi-layer composite system, the aging resistance of the bronze powder is improved, and meanwhile, the optical decoration performance can be reserved to the maximum extent, so that the dual strict requirements of high-end outdoor applications such as automobile coatings on durability and visual texture can be met.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of copper gold powder pigments, and particularly relates to a kind of anti-aging copper gold powder pigments and its preparation method and application. BACKGROUND

[0002] The copper gold powder pigments have been widely used in many fields such as silk screen printing, printing packaging, paint, ink, coating, handicraft and toy manufacturing due to its unique metallic luster and gorgeous decorative effect. The core component of copper zinc alloy can provide a series of rich gold color tones from red gold, green gold to green gold, which meets the market's pursuit of luxurious appearance.

[0003] However, the traditional copper gold powder in the prior art has poor environmental aging resistance, especially insufficient ultraviolet aging resistance. This defect greatly limits the application of copper gold powder pigments in high-value and high-demand fields. In particular, in the automobile manufacturing industry, the metallic flash finish requires that the pigments not only have a brilliant metallic flash effect and goniochromism, but also must have long-term durability under extremely harsh conditions. In addition, the automobile paint surface is exposed to the outdoors all year round, and is subjected to strong ultraviolet radiation, severe temperature changes, rain, acid rain erosion and salt spray environment. The traditional copper gold powder cannot completely meet these requirements.

[0004] At present, the surface treatment is mostly adopted to solve the problem of poor aging resistance of copper gold powder, but there are many defects: first, the protective efficiency and durability are insufficient. For example, the conventional organic passivation film (such as benzotriazole BTA film) has poor ultraviolet resistance and is easily degraded by light under long-term sunlight, and its heat resistance cannot withstand the baking and curing temperature of automobile coatings above 140°C, resulting in rapid degradation of the protection function. In addition, a single inorganic passivation layer (such as silicate, phosphate) has micro defects and cannot effectively block the penetration of water vapor, oxygen and sulfides; second, the interface bonding force between the protective layer and the metal substrate is weak. The protective layer and the copper substrate are mainly combined by physical adsorption or weak intermolecular forces, which are easy to peel off between the layers under the conditions of wet heat, cold heat cycle or mechanical shear stress, resulting in protection failure; third, it is difficult to balance the long-term ultraviolet resistance and physical barrier performance. Ordinary ultraviolet absorbers and light stabilizers added by blending are easy to migrate and precipitate, which cannot provide long-lasting protection. Relying only on thickening the physical barrier layer will sacrifice the metallic luster and optical effect of the copper gold powder; fourth, it is difficult to balance environmental protection and high performance. High-efficiency but toxic chromium salt passivation process is limited by environmental regulations, and the comprehensive protection performance of the existing environmental protection alternative scheme often cannot meet the harsh requirements of automobile coatings.

[0005] The root cause is that the traditional process focuses on the adjustment of physical properties such as color and particle size, and does not fundamentally solve the core problems such as easy ozone oxidation and lattice structure damage of copper gold powder under the action of ultraviolet light. There is a lack of functional substances that can absorb / reflect ultraviolet light and self-repair mechanism. SUMMARY

[0006] The present application aims at the existing technical problems, and proposes a kind of anti-aging copper gold powder pigment and its preparation method and application, under the premise of environmental protection, through the innovative design of multilayer composite system, synchronous realization of extreme weather resistance, super strong interlayer adhesion, persistent active ultraviolet resistance function and excellent metal optical effect, to meet the dual requirements of durability and appearance of automobile original factory paint.

[0007] The present application realizes the above-mentioned purposes by the following technical schemes: As a first aspect of the present application, a kind of anti-aging copper gold powder pigment is provided, the anti-aging copper gold powder pigment is with copper-zinc alloy as substrate, sequentially connected with composite chemical passivation layer, functional organic-inorganic hybrid dense barrier layer and surface superhydrophobic layer by chemical bonding from inside to outside;Wherein, The composite chemical passivation layer is formed by treating the passivation solution containing phytic acid, ammonium metavanadate and sodium tungstate; The functional organic-inorganic hybrid dense barrier layer is constructed by silane mixed solution containing 3-mercaptopropyl triethoxysilane, reactive ultraviolet absorber Si-BP, reactive hindered amine light stabilizer Si-HALS and tetraethyl orthosilicate by sol-gel process; The surface superhydrophobic layer is formed by grafting modification of fluorinated POSS hydrophobic agent.

[0008] As a further optimization scheme of the present application, in the passivation solution, phytic acid is 3-5 parts by weight, ammonium metavanadate is 0.8-1.2 parts by weight, and sodium tungstate is 1.2-1.8 parts by weight, and the solvent is 40-60 parts by weight of water.

[0009] As a further optimization scheme of the present application, in the silane mixed solution, 3-mercaptopropyl triethoxysilane is 2-4 parts by weight, reactive ultraviolet absorber Si-BP is 1.2-1.8 parts by weight, reactive hindered amine light stabilizer Si-HALS is 1.2-1.8 parts by weight, and tetraethyl orthosilicate is 7-9 parts by weight, and the solvent is 30-50 parts by weight of isopropanol.

[0010] As a further optimization scheme of the present application, the weight ratio of fluorinated POSS hydrophobic agent to copper-zinc alloy is 1-3:80-120.

[0011] As a second aspect of the present application, the application of the anti-aging copper gold powder pigment as described in any one of the above in the field of automobile paint is also provided.

[0012] As a third aspect of the present application, a preparation method of the anti-aging copper gold powder pigment as described in any one of the above is also provided, comprising the following steps: The pretreated copper-zinc alloy is dispersed in deionized water, heated in a water bath and stirred, the pH of the system is adjusted to 3.0-4.0, the passivation solution is slowly added into the reaction system, constant temperature reaction is carried out, the pH of the system is adjusted to 6.5-7.5, and the composite chemical passivation layer is formed by continuing the reaction, and then the filter cake is filtered, washed to neutral, and dried in a vacuum oven. (2) The wet filter cake is dispersed in an isopropanol aqueous solution, a catalyst solution is added, heated in a water bath and stirred, the silane mixture is slowly added into the reaction system, and the functionalized organic-inorganic hybrid dense barrier layer is formed by reaction after temperature rising; (3) The reaction system of step (2) is kept, a fluorinated POSS hydrophobic agent is added, and the superhydrophobic surface modification layer is formed by reaction after temperature rising; (4) The reaction system is cooled to room temperature, and then the filter cake is filtered, washed, dried in a vacuum and sieved to obtain the copper gold powder pigment.

[0013] As a further optimization scheme of the application, in step (1), the pretreatment is that 80-120 parts by weight of copper-zinc alloy is added into 400-600 parts by weight of organic solvent, ultrasonic dispersion is carried out for 20-40 min, and then filtration is carried out, the filter cake is washed with organic solvent for 1-3 times, and dried in a vacuum oven at 70-90 ℃ for 3-5 h, and then used.

[0014] As a further optimization scheme of the application, in step (1), the weight ratio of deionized water to copper-zinc alloy is 300-500:80-120.

[0015] As a further optimization scheme of the application, in step (1), the water bath heating temperature is 50-70 ℃, the constant temperature reaction time is 20-40 min, and the continuous reaction time is 20-40 min.

[0016] As a further optimization scheme of the application, in step (2), the catalyst solution is that ammonia water with a mass concentration of 25-30 % and isopropanol are mixed in a volume ratio of 3-5:12-20.

[0017] As a further optimization scheme of the application, in step (2), the water bath heating temperature is 40-50 ℃, the temperature is raised to 45-55 ℃, and the reaction is carried out for 6-10 h.

[0018] As a further optimization scheme of the application, in step (3), the temperature is raised to 55-65 ℃, and the reaction is carried out for 2-4 h.

[0019] The application has the following beneficial effects: (1) The present application breaks through the limitation of traditional single layer / simple layer protection, constructs a four-layer structure of "flaky copper-zinc alloy substrate-composite chemical passivation layer-functionalized organic-inorganic hybrid dense barrier layer-super-hydrophobic surface modification layer", and each layer is complementary to form a whole chain protection of "bottom layer corrosion resistance-middle layer UV resistance / scuff resistance-surface layer moisture resistance", which solves the problems of easy oxidation, poor weather resistance, and the incompatibility of optical performance and protective performance of copper and gold powder from the root; (2) The present application innovatively permanently anchors the reactive ultraviolet absorber Si-BP and the reactive hindered amine light stabilizer Si-HALS in the organic-inorganic hybrid network through covalent bond, which not only avoids the protection attenuation caused by the loss of traditional free additives during use, but also realizes the synergistic anti-ultraviolet effect of "ultraviolet absorption+chemical repair" through the targeted strengthening of Si-BP on the ultraviolet region absorption which is significant to the photo-oxidation damage of copper and gold powder and the efficient capture of Si-HALS on photoaging free radicals; (3) The present application realizes the firm combination of flaky copper-zinc alloy substrate and composite chemical passivation layer through "phytic acid chelation + vanadium / tungstate co-deposition", anchors the composite chemical passivation layer and the functionalized organic-inorganic hybrid dense barrier layer by using the mercapto group (-SH) of MPTES to form Cu-S covalent bond with the substrate, and relies on the Si-O-Si covalent bond to build the three-dimensional network inside the functionalized organic-inorganic hybrid dense barrier layer and the connection between the functionalized organic-inorganic hybrid dense barrier layer and the surface super-hydrophobic layer (fluorinated POSS), which completely solves the bottleneck of the traditional protection system which relies on physical adsorption and is easy to peel off between layers; (4) The present application adopts a nanoscale ultrathin protective layer design, which realizes extreme aging resistance protection through multiple mechanisms while maximizing the retention of the mirror reflection characteristics and metal decoration texture of copper and gold powder, effectively resolves the technical problem that "aging resistance performance improvement" and "optical decoration performance maintenance" cannot be compatible, and finally realizes the synergy of "high aging resistance + high decoration", which fully meets the dual harsh requirements of durability and visual texture for high-end outdoor applications such as automotive coatings. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 The SEM image of the copper and gold powder pigment obtained in Example 1 provided by the present application; Figure 2 The TEM image of the copper and gold powder pigment obtained in Example 1 provided by the present application; Figure 3 The sample plate comparison chart of the copper and gold powder pigment obtained in Example 1 provided by the present application and the coating sample prepared by the flaky copper-zinc alloy without any treatment, which is obtained by spraying and high-temperature baking. DETAILED DESCRIPTION

[0021] Further detailed description of the present application is made below, it is necessary to point out here that the following specific embodiments are only used to further illustrate the present application, and cannot be understood as limiting the scope of protection of the present application, and the skilled in the art can make some non-essential improvements and adjustments to the present application according to the above application content.

[0022] The substrate is a flaky copper-zinc alloy powder pigment with a particle size of 15-25 μm, Cu: 70 %±1 %, Zn: 30 %±1 %; The passivation solution is prepared by dissolving phytic acid 3-5 parts, ammonium metavanadate 0.8-1.2 parts, sodium tungstate 1.2-1.8 parts in 40-60 parts of warm water, and mixing; The silane mixed solution is prepared by dissolving 3-mercapto propyl triethoxysilane MPTES 2-4 parts, reaction type ultraviolet absorber Si-BP 1.2-1.8 parts, reaction type hindered amine light stabilizer Si-HALS 1.2-1.8 parts, and tetraethyl orthosilicate TEOS 7-9 parts in 30-50 parts of isopropanol, and stirring uniformly to obtain; The catalyst solution is prepared by mixing 3-5 mL of ammonia water (mass concentration of 25-30 %) and 12-20 mL of isopropanol.

[0023] The methods used in the present application are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products, unless otherwise specified.

[0024] Example 1 The anti-aging copper gold powder pigment provided in the present embodiment is prepared by sequentially modifying a flaky copper-zinc alloy with a composite chemical passivation layer, a functionalized organic-inorganic hybrid dense barrier layer and a surface super-hydrophobic layer from inside to outside on its surface, and the preparation method comprises the following steps: (1) Pretreatment: take 100 parts by weight of flaky copper-zinc alloy powder pigment, add 500 parts by weight of isopropanol, ultrasonic dispersion for 30 min, filter, wash twice with isopropanol, and dry in a vacuum oven at 80 ℃ for 4 h, and reserve; (2) Composite chemical passivation layer modification: First, weigh 4 parts by weight of phytic acid, 1 part by weight of ammonium metavanadate, and 1.5 parts by weight of sodium tungstate, and dissolve them in 50 parts by weight of 40°C warm water to prepare a passivation solution. Then, disperse the pretreated flaky copper-zinc alloy powder pigment in 400 parts by weight of deionized water, heat in a water bath to 60°C, and mechanically stir at 250 rpm. Add a 5% by volume dilute nitric acid solution to adjust the pH of the system to 3.5, then slowly add the passivation solution to the reaction system through a constant-pressure dropping funnel within 30 min, maintain a constant temperature of 60°C for 30 min, finally adjust the pH of the system to 7.0 with a 5% by volume sodium hydroxide solution, and continue to react for 30 min. After the reaction is completed, filter and wash the filter cake with deionized water until it is neutral to obtain a passivation intermediate; (3) Functional organic-inorganic hybrid dense barrier layer modification: Mix 3 ml of 25% ammonia water with 12 ml of isopropyl alcohol to prepare a catalyst solution. Weigh 3 parts by weight of MPTES, 1.5 parts by weight of Si-BP, 1.5 parts by weight of Si-HALS, and 8 parts by weight of TEOS, and dissolve them in 30 parts by weight of isopropyl alcohol to obtain a silane mixture. Disperse the passivation intermediate in 300 parts by weight of a mixed solvent of isopropyl alcohol / water (volume ratio 4:1), first add the catalyst to the reaction system, heat in a water bath to 45°C, and stir, then slowly add the silane mixture to the reaction system at a constant speed within 90 min, and after the addition is completed, increase the temperature to 50°C, and maintain a constant temperature for 8 h to obtain a functional intermediate; (4) Surface super-hydrophobic layer modification: Maintain the reaction system of step (3), add 2 parts by weight of fluorinated POSS hydrophobic agent, increase the temperature to 60°C, and continue to react for 3 h. After the reaction is completed, cool to room temperature, filter, wash the filter cake with anhydrous isopropyl alcohol 3 times, dry the filter cake in a 80°C vacuum drying oven for 12 h, and sieve through an 800 mesh sieve to obtain an anti-aging copper-gold powder pigment.

[0025] Example 2 The present embodiment provides a method for preparing an anti-aging copper-gold powder pigment, comprising the following steps: (1) Pretreatment: Take 80 parts by weight of flaky copper-zinc alloy powder pigment, add 400 parts by weight of isopropyl alcohol, ultrasonically disperse for 20 min, filter, wash twice with isopropyl alcohol, and dry in a 70°C vacuum oven for 3 h for standby use; (2) Composite chemical passivation layer modification: First, weigh 3 parts by weight of phytic acid, 0.8 parts by weight of ammonium metavanadate, and 1.2 parts by weight of sodium tungstate, and dissolve them in 40 parts by weight of 40°C warm water to prepare a passivation solution. Then, disperse the pretreated flaky copper-zinc alloy powder pigment in 300 parts by weight of deionized water, heat the water bath to 50°C, and mechanically stir at 250 rpm. Add a 5% volume fraction of dilute nitric acid solution to adjust the pH of the system to 3.0. Then, slowly add the passivation solution to the reaction system through a constant-pressure dropping funnel within 20 min, maintain a constant temperature of 50°C for 20 min, finally adjust the pH of the system to 6.5 with a 3% volume fraction of sodium hydroxide solution, and continue to react for 20 min. After the reaction is completed, filter and wash the filter cake with deionized water until it is neutral to obtain a passivation intermediate; (3) Functionalized organic-inorganic hybrid dense barrier layer modification: Mix 3 ml of ammonia water (25% mass concentration) with 12 ml of isopropyl alcohol to prepare a catalyst solution. Weigh 2 parts by weight of MPTES, 1.2 parts by weight of Si-BP, 1.2 parts by weight of Si-HALS, and 7 parts by weight of TEOS, and dissolve them in 30 parts by weight of isopropyl alcohol to obtain a silane mixture. Disperse the passivation intermediate in 250 parts by weight of a mixed solvent of isopropyl alcohol / water (volume ratio of 3:1). First, add the catalyst to the reaction system, heat the water bath to 40°C, and stir. Then, slowly add the silane mixture to the reaction system at a constant speed within 60 min. After the addition is completed, increase the temperature to 45°C, and maintain the constant temperature for 6 h to obtain a functionalized intermediate. (4) Surface super-hydrophobic modification: Maintain the reaction system of step (3), add 1 part by weight of fluorinated POSS hydrophobic agent, increase the temperature to 55°C, and continue to react for 2 h. After the reaction is completed, cool to room temperature, filter, wash the filter cake with anhydrous ethanol for 2 times, dry the filter cake in a 70°C vacuum drying oven for 10 h, and pass through an 800 mesh sieve to obtain the anti-aging copper-gold powder pigment.

[0026] Example 3 The present embodiment provides a preparation method of an anti-aging copper-gold powder pigment, comprising the following steps: (1) Pretreatment: Take 120 parts by weight of flaky copper-zinc alloy powder pigment, add 600 parts by weight of isopropyl alcohol, ultrasonically disperse for 40 min, filter, wash with isopropyl alcohol for 2 times, and dry in a 90°C vacuum oven for 5 h for standby use. (2) Composite chemical passivation layer modification: First, weigh 5 parts by weight of phytic acid, 1.2 parts by weight of ammonium metavanadate, and 1.8 parts by weight of sodium tungstate, and dissolve them in 60 parts by weight of 40°C warm water to prepare a passivation solution. Then, disperse the pretreated flaky copper-zinc alloy powder pigment in 500 parts by weight of deionized water, heat the water bath to 70°C, and mechanically stir at 350 rpm. Add a 7% volume fraction of dilute nitric acid solution to adjust the system pH to 4.0, then slowly add the passivation solution to the reaction system through a constant-pressure dropping funnel within 40 minutes, maintain a constant temperature of 70°C for 40 minutes, finally adjust the system pH to 7.5 with a 7% volume fraction of sodium hydroxide solution, and continue to react for 40 minutes. After the reaction is completed, filter and wash the filter cake with deionized water until it is neutral to obtain a passivation intermediate; (3) Functional organic-inorganic hybrid dense barrier layer modification: Mix 3 ml of ammonia water (25% mass concentration) with 12 ml of isopropyl alcohol to prepare a catalyst solution. Weigh 4 parts by weight of MPTES, 1.8 parts by weight of Si-BP, 1.8 parts by weight of Si-HALS, and 9 parts by weight of TEOS, and dissolve them in 50 parts by weight of isopropyl alcohol to obtain a silane mixture. Disperse the passivation intermediate in 350 parts by weight of a mixed solvent of isopropyl alcohol and water (volume ratio 5:1), add the catalyst to the reaction system, heat the water bath to 50°C, and stir. Then, slowly add the silane mixture to the reaction system at a constant speed within 120 minutes, and then heat to 55°C for constant temperature reaction for 10 hours to obtain a functional intermediate. (4) Surface super-hydrophobic layer modification: Keep the reaction system of step (3), add 3 parts by weight of fluorinated POSS hydrophobic agent, heat to 65°C, and continue to react for 4 hours. After the reaction is completed, cool to room temperature, filter, wash the filter cake with anhydrous isopropyl alcohol for 2 times, place the filter cake in a 90°C vacuum drying oven for drying for 14 hours, and pass through a 900 mesh sieve to obtain the anti-aging copper-gold powder pigment.

[0027] To explore the effects of composite chemical passivation layer modification, functional organic-inorganic hybrid dense barrier layer modification, and surface super-hydrophobic layer modification on the properties of copper-gold powder pigment, the following comparative examples are provided: Comparative Example 1 The difference between this comparative example and Example 1 is that the anti-aging copper-gold powder pigment provided by this comparative example is not subjected to surface super-hydrophobic layer modification. That is, after obtaining the functional intermediate during the preparation of the copper-gold powder pigment, cool to room temperature, filter, wash the filter cake with anhydrous isopropyl alcohol for 2 times, place the filter cake in a 80°C vacuum drying oven for drying for 12 hours, and pass through a 800 mesh sieve.

[0028] Comparative Example 2 In the present comparative example, the composition of the passivation solution used in step (2) of Example 1 was adjusted. The passivation solution used in the present comparative example was prepared by dissolving 4 parts by weight of phytic acid, 1 part by weight of ammonium molybdate and 1.5 parts by weight of sodium tungstate in 50 parts by weight of warm water.

[0029] Comparative Example 3 In the present comparative example, the composition of the silane mixture used in step (3) of Example 1 was adjusted. The silane mixture used in the present comparative example was prepared by dissolving 3 parts by weight of MPTES and 8 parts by weight of TEOS in 30 parts by weight of isopropanol.

[0030] Comparative Example 4 In the present comparative example, the composition of the silane mixture used in step (3) of Example 1 was adjusted. The silane mixture used in the present comparative example was prepared by dissolving 3 parts by weight of MPTES, 8 parts by weight of TEOS and 3 parts by weight of Si-BP in 30 parts by weight of isopropanol.

[0031] Comparative Example 5 In the present comparative example, the composition of the silane mixture used in step (3) of Example 1 was adjusted. The silane mixture used in the present comparative example was prepared by dissolving 3 parts by weight of MPTES, 8 parts by weight of TEOS and 3 parts by weight of Si-HALS in 30 parts by weight of isopropanol.

[0032] Comparative Example 6 The difference between the present comparative example and Example 1 is that the anti-aging copper-gold powder pigment provided in the present comparative example was not modified with a functional organic-inorganic hybrid dense barrier layer. That is, in the preparation of the copper-gold powder pigment, step (3) was not performed. After the washing and suction filtration in step (2), the filter cake was redissolved in anhydrous isopropanol and stirred. Then, 2 parts by weight of the fluorinated POSS hydrophobic agent was added thereto, the temperature was raised to 60°C, and the reaction was continued for 3 hours. After the reaction was completed, the temperature was cooled to room temperature, suction filtration was performed, the filter cake was washed with anhydrous isopropanol for 3 times, the filter cake was dried in a vacuum drying oven at 80°C for 12 hours, and was sieved through an 800-mesh sieve.

[0033] Comparative Example 7 The difference between the present comparative example and Example 1 is that the anti-aging copper-gold powder pigment provided in the present comparative example was not modified with a functional organic-inorganic hybrid dense barrier layer and a surface super-hydrophobic layer. That is, after the passivation intermediate was obtained, it was directly placed in a vacuum drying oven at 80°C for 12 hours, and was sieved through an 800-mesh sieve.

[0034] Comparative Example 8 In this comparative example, the passivation solution in Example 1, Step (2) was adjusted. The passivation solution used in this comparative example was 2 parts by weight of BTA dissolved in 30 parts by weight of anhydrous isopropyl alcohol and mixed well.

[0035] The pretreated flaky copper-gold powder alloy was dispersed in 400 parts by weight of anhydrous isopropyl alcohol, heated in a water bath to 60°C, and mechanically stirred at 250 rpm. The passivation solution was slowly added to the reaction system over 30 min using a constant pressure dropping funnel, and the reaction was maintained at 60°C for 60 min. After the reaction was completed, the mixture was suction filtered and the filter cake was washed twice with anhydrous isopropyl alcohol to obtain the passivated intermediate. The remaining steps were the same as in Example 1 to obtain the copper-gold powder pigment.

[0036] The copper-gold powder pigments obtained in Examples 1-3 and Comparative Examples 1-8 were subjected to the following performance tests: SEM and TEM tests The copper-gold powder pigment obtained in Example 1 was selected for SEM and TEM tests. The test results are shown in FIGS. 1-2. Figures 1-2 As shown in FIGS. 1-2, the copper-gold powder pigment had a uniform and dense coating structure, achieving complete protection of the surface.

[0037] (2) Gloss performance test The copper-gold powder pigments prepared in Examples 1-3 and Comparative Examples 1-8 were mixed uniformly according to the ratio of copper-gold powder pigment: dispersant (butyl glycol): varnish (water-based polyurethane resin) = 1:1.5:7.5 (mass ratio) to obtain paint. The paint was used to prepare a 50 μm paint film on a sample plate using a four-sided applicator. After drying at room temperature, the sample plate was obtained. A BYK 60° gloss meter was used to test 5 points on each plate after calibration, and the average value was taken. In addition, a flaky copper-zinc alloy without any treatment (blank control) was also prepared into paint and sample plate, and subjected to gloss performance test.

[0038] The test results are shown in Table 1.

[0039] Table 1, Gloss performance test results ; As can be seen from Table 1, the luster performance of Examples 1-3 is significantly better than that of Comparative Examples, the 60° gloss can reach more than 85%, and the copper gold powder pigments of Examples 1-3 are constructed with a four-layer structure of "flaky copper-zinc alloy substrate-composite chemical passivation layer-functionalized organic-inorganic hybrid dense barrier layer-super-hydrophobic surface modification layer". The amount of fluorinated POSS hydrophobic agent used in the outermost layer of Example 2 is less and the modification reaction conditions are relatively mild, which leads to insufficient grafting density and regularity of POSS molecules on the particle surface, resulting in insufficient super-hydrophobic properties. When applied to a water-based paint system, this defective hydrophobic layer cannot provide sufficient and uniform repulsive force for the copper gold powder, thereby affecting the directional arrangement and floating property of the pigment during the film-forming process, ultimately leading to a decrease in the surface flatness of the paint film and a decrease in the metallic luster. However, the gloss is still significantly better than that of the comparative examples.

[0040] (2) Salt fog resistance test Take the copper gold powder pigments obtained in Examples 1-3 and Comparative Examples 1-8, mix them uniformly according to copper gold powder pigment: dispersion (ethylene glycol butyl ether): varnish (water-based acrylic resin) = 1:1.5:7.5 (mass ratio), finally, add deionized water (mass ratio of copper gold powder to deionized water is 1:3) to adjust the viscosity, obtain the corresponding paint samples, first spray epoxy primer (about 20 μm) on the cleaned tinplate plate (substrate) (70×150×1 mm), room temperature curing for 24 h, then spray copper gold powder coating (about 30 μm), 150 ℃ drying for 30 min, test the coating according to the joint test scheme and rating process of "GB / T 10125-1997 Salt Spray Test" and "GB / T 30789-2015 Paints and Varnishes Evaluation of Corrosion Resistance of Coatings", in addition, take the flaky copper-zinc alloy without any treatment as a blank control, prepare paint samples and spray the plate according to the same operation as above: Experimental conditions: the experiment is carried out in a BGD881 salt spray corrosion test box, the salt spray type is continuous spraying, the duration is 240 h; the test temperature is controlled at 35±1 ℃, the pressure barrel and the salt water barrel are maintained at 36 ℃ and 35 ℃ respectively; the salt water used for spraying is 5.0±0.1 % NaCl solution (analytical pure), the pH is 6.5-7.2, the conductivity of distilled water is 1.76 mS / m, the salt spray deposition is 1.0-2.0 mL / 80 cm 2 h; the air pressure in the box is maintained at 1.0 kPa, the relative humidity of the machine environment is ≤85%; the test sample is placed in the box at an inclination angle of 15°.

[0041] The detection indexes are as follows: ① Adhesion loss rate (peeling area of coating %): adopt grid method after salt spray, reference standard is GB / T 9286; calculation formula is as follows: ; 2. Color difference AE, 5 points before / after salt spray, L, a, b values were measured; the calculation formula is as follows: ; 3. Foaming density: 1 cm 2 area was observed under a microscope, and the number of bubbles was counted. 2 The calculation formula is as follows: ; 4. Cracking grade: The evaluation standard of cracking grade is shown in Table 2, and 1 cm 2 area was observed under a digital microscope at 200x, and the number of cracks and the width were counted, and the cracking area ratio was calculated according to the following formula: ; 5. Corrosion grade (Ri): The rating standard of corrosion grade is shown in Table 3.

[0042] Table 2, Evaluation standard of cracking grade ; Table 3, Rating standard of corrosion grade (Ri) ; The salt spray resistance test results of the copper-gold powder pigments obtained in Examples 1-3 and Comparative Examples 1-8 and the untreated flaky copper-zinc alloy (blank control) are shown in Table 4.

[0043] Table 4, Salt spray resistance test results ; As can be seen from Table 4, the salt spray resistance of the copper-gold powder pigments of Examples 1-3 is significantly better than that of the comparative examples. Comparative Example 1 is not modified with a super-hydrophobic layer, resulting in insufficient super-hydrophobic properties. When applied to a water-based paint system, this defective hydrophobic layer cannot provide sufficient and uniform repulsive force for the copper-gold powder, resulting in a significant decrease in salt spray resistance compared to the examples. The core reason for the poor salt spray resistance of Comparative Examples 2-8 is that the construction of the "functionalized organic-inorganic hybrid dense barrier layer" is defective. The barrier layer that is not dense enough cannot effectively block the penetration of chloride ions, water vapor and oxygen, and the corrosion medium easily reaches the bottom layer and causes the coating to blister, peel and the substrate to corrode.

[0044] (3) Aging resistance test The copper-gold powder pigments obtained in Examples 1-3 and Comparative Examples 1-8 were mixed uniformly according to copper-gold powder pigment: black plastic powder = 1:19 (mass ratio) by high shear, and paint samples were obtained. Each paint sample was sprayed on an aluminum alloy plate by electrostatic spraying (70 kV), and the plate was prepared by curing at 230°C for 10 min.

[0045] In addition, the flaky copper-zinc alloy without any treatment was used as a blank control, and the coating sample was prepared according to the same operation as above.

[0046] Figure 3 As can be seen from the comparison of the sample plates prepared by spraying and high-temperature baking of the coating sample prepared from the copper-gold powder pigment obtained in Example 1 and the flaky copper-zinc alloy without any treatment, the flaky copper-zinc alloy without any treatment is not resistant to high temperature, and the electrostatic spraying plate will become black after baking at 230°C, and the metallic luster of the copper-gold powder decreases.

[0047] The anti-aging performance test method is carried out according to the standard GSB-AL-631-2017, and the sample size is 100x150 mm aluminum alloy plate (coating thickness 60±5 μm); the test is carried out in a Q-SUN Xe-3-HS xenon lamp aging box, and the lamp type is UVB-313 (ultraviolet wave band peak 310 nm); the cycle program is as follows: (A) ultraviolet stage: 4 h irradiation, blackboard temperature (50±3) °C, irradiance (0.75±0.02) W / m 2 @310 nm; (B) condensation stage: 4 h condensation, box temperature (40±3) °C, relative humidity >95%; (C) alternating cycle: 1 cycle (ultraviolet 4 h→condensation 4 h) every 8 h, total test time 1000 h (125 cycles).

[0048] The detection indexes are as follows: ① Color difference ΔE, 5 points before and after aging to measure L, a, b values, L1, a1, b1; the calculation formula is as follows: ; In the formula: L1, a1, b1 are the data before aging; L2, a2, b2 are the data after aging; ② Light loss rate: 5 points before and after aging to measure 60° gloss, the calculation formula is as follows: ; In the formula: G0 is the 60° gloss data before aging; G t is the 60° gloss data after aging; ③ Powdering grade: the transparent pressure-sensitive tape (adhesion 10±1 N / 25 mm) is pressed on the coating surface, and the powder particles adhered to the tape are observed after being vertically torn off. The gray scale difference (ΔW) before and after the tape is measured by a whiteness meter, the powdering degree is calculated, and the evaluation standard of the powdering grade is shown in Table 5; ④ The evaluation standard of cracking grade is shown in Table 2, and the number and width of cracks are counted under the observation of a digital microscope scanning 1 cm 2 area at 200x, and the cracking area ratio calculation formula is as follows: .

[0049] Table 5, powdering rating rating standard ; The results of the anti-aging performance test of the copper-gold powder pigment samples of Examples 1-3, Comparative Examples 1-8 and the blank control group are shown in Table 6.

[0050] Table 6, anti-aging performance test results ; As can be seen from the table, the anti-aging performance of the copper-gold powder pigments of Examples 1-3 is better than that of the comparative examples. Analysis of the preparation methods of the comparative examples and the examples shows that the defects in the construction of the “functionalized organic-inorganic hybrid dense barrier layer” also play a dominant role in the light aging performance; in addition, the deficiency of the hydrophobic layer also makes water more easily attached and involved in the light aging process, which together accelerates the photo-oxidative degradation of the pigment and the powdering of the coating.

[0051] Based on the results of the above performance tests, the following conclusions are drawn: The copper-gold powder pigment of the present application is composed of the following four layers from inside to outside: flaky copper-zinc alloy (substrate), composite chemical passivation layer, functionalized organic-inorganic hybrid dense barrier layer, and surface super-hydrophobic layer; Firstly, the composite chemical passivation layer is formed by treating the passivation solution prepared from phytic acid, ammonium metavanadate and sodium tungstate, and the firm combination of the substrate and the composite chemical passivation layer is achieved through “phytic acid chelation + vanadium / tungstate co-deposition”; Secondly, the functionalized organic-inorganic hybrid dense barrier layer is constructed by the silane mixed solution prepared from MPTES, Si-BP, Si-HALS and TEOS through sol-gel process, covalently anchoring the reactive ultraviolet absorber Si-BP and the reactive hindered amine light stabilizer Si-HALS in the organic-inorganic hybrid network, which not only completely avoids the attenuation of the protection function caused by the loss of the additive, but also effectively blocks the ultraviolet light from deteriorating the copper substrate and the coating layer through the targeted strengthening of the ultraviolet region absorption of Si-BP which is significantly damaged by the photo-oxidation of copper gold powder, and the high-efficiency capture of various free radicals generated in the photo-aging process by Si-HALS, forming a full-chain protection of “ultraviolet spectrum absorption + chemical damage repair”. In addition, through the strong Cu-S covalent bond formed between the mercapto-containing silane coupling agent MPTES and the surface of the flaky copper-zinc alloy (substrate), the molecular-level anchoring of the protection system and the substrate is achieved, which, combined with the three-dimensional dense network constructed by the Si-O-Si covalent bond inside the functionalized organic-inorganic hybrid dense barrier layer, greatly improves the structural stability and long-term integrity of the protection system, which is conducive to solving the bottleneck of the existing protection system and copper substrate which mainly rely on physical adsorption or weak hydrogen bond combination, and easily peeling off between layers under long-term outdoor aging, leading to the failure of protection. Finally, the surface super-hydrophobic layer is formed by grafting modification of the fluorinated POSS hydrophobic agent, and the functions of each layer are complementary to form a full-chain protection of "bottom layer anti-corrosion - middle layer anti-UV / scratch-resistant - surface layer anti-wetting dirt", which solves the problems of easy oxidation, poor weather resistance, and the incompatibility of optical performance and protective performance of copper and gold powder from the root.

[0052] The above-described embodiments only express several embodiments of the present application, which are described in a more specific and detailed manner, but should not be understood as a limitation to the scope of the patent of the present application. It should be noted that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present application, which are all within the protection scope of the present application.

Claims

1. An age-resistant copper gold powder pigment, characterized in that, The anti-aging copper gold powder pigment takes copper-zinc alloy as a substrate, and sequentially has a composite chemical passivation layer, a functionalized organic-inorganic hybrid dense barrier layer and a surface super-hydrophobic layer connected by chemical bonding from inside to outside, wherein The composite chemical passivation layer is formed by treating the passivation solution containing phytic acid, ammonium metavanadate and sodium tungstate; The functionalized organic-inorganic hybrid dense barrier layer is constructed by sol-gel process of the silane mixed solution containing 3-mercaptopropyl triethoxysilane, reactive ultraviolet absorber Si-BP, reactive hindered amine light stabilizer Si-HALS and tetraethyl orthosilicate; The surface super-hydrophobic layer is formed by grafting modification of the fluorinated POSS hydrophobic agent.

2. The weather resistant copper gold powder pigment according to claim 1, characterized in that, In the passivation solution, the phytic acid is 3-5 parts by weight, the ammonium metavanadate is 0.8-1.2 parts by weight, the sodium tungstate is 1.2-1.8 parts by weight, and the solvent is 40-60 parts by weight of water.

3. The weatherable copper gold pigment according to claim 1, wherein, In the silane mixed solution, the 3-mercaptopropyl triethoxysilane is 2-4 parts by weight, the reactive ultraviolet absorber Si-BP is 1.2-1.8 parts by weight, the reactive hindered amine light stabilizer Si-HALS is 1.2-1.8 parts by weight, the tetraethyl orthosilicate is 7-9 parts by weight, and the solvent is 30-50 parts by weight of isopropanol.

4. The weatherable copper gold pigment according to claim 1, wherein, The weight ratio of the fluorinated POSS hydrophobic agent to the copper-zinc alloy is 1-3:80-120.

5. The anti-aging copper gold powder pigment according to any one of claims 1-4 is applied in the field of automobile coatings.

6. The method of claim 1-4, wherein the method is characterized by, The method comprises the following steps: (1) dispersing the pretreated copper-zinc alloy in deionized water, heating and stirring in a water bath, adjusting the pH of the system to 3.0-4.0, slowly adding the passivation solution to the reaction system, adjusting the pH of the system to 6.5-7.5, continuing to react to form a composite chemical passivation layer, and then filtering, washing the filter cake to neutral; (2) dispersing the wet filter cake in an isopropanol aqueous solution, adding a catalyst solution, heating and stirring in a water bath, slowly adding the silane mixed solution to the reaction system, and then reacting to form a functionalized organic-inorganic hybrid dense barrier layer after heating; (3) maintaining the reaction system of step (2), adding a fluorinated POSS hydrophobic agent, and then reacting to form a super-hydrophobic surface modification layer after heating; (4) cooling the reaction system to room temperature, then filtering, washing the filter cake, vacuum drying and sieving to obtain a copper gold powder pigment.

7. The method of claim 6, wherein the method further comprises the step of adding a dispersant to the mixture of copper and gold particles. In step (1), the weight ratio of the deionized water to the copper-zinc alloy is 300-500:80-120.

8. The method of claim 6, wherein the method is characterized by, In step (2), the catalyst solution is a mixture of 25-30 % ammonia water and isopropanol in a volume ratio of 3-5:12-20.

9. The method for preparing an aging-resistant copper-gold powder pigment according to claim 6, characterized in that, In step (2), the water bath heating temperature is 40-50 ℃, the temperature is raised to 45-55 ℃, and the reaction is carried out for 6-10 h.

10. The method of claim 6, wherein the method is characterized by: In step (3), the temperature is raised to 55-65 ℃, and the reaction is carried out for 2-4 h.

Citation Information

Patent Citations

  • Aqueous bronze powder preparation method

    CN103333532A

  • Preparation method of organic-inorganic double-cladding water-borne bronze powder

    CN105968887A

  • Preparation method of high-gloss and corrosion-resistant water-based bronze powder

    CN112427636A

  • Aluminum powder pigment with three-layer coating structure and preparation method of aluminum powder pigment

    CN120535975A

  • Gold powder for gold ink

    JP1995278462A

Cited By

  • Anti-fatigue bronze powder pigment for anti-counterfeit printing as well as preparation method and application of anti-fatigue bronze powder pigment

    CN121673861A